MOTIVASI DAN KINERJA GURU DALAM MENINGKATKAN MUTU PENDIDIKAN DI MTS AL-ANWAR KABUPATEN OKU TIMUR - Khasanah, Uswatun; Patimah, Siti; Bedi, Fisman; Ghani; Latief Arung Arafah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze the effect of motivation on teacher performance in improving the quality of education at Mts Al-Anwar. In the context of education, teacher motivation plays a crucial role in determining the quality of teaching and, ultimately, student achievement. This study used a quantitative descriptive method with a sample of 30 teachers randomly drawn from the total population. Data were collected through a questionnaire measuring aspects of intrinsic and extrinsic motivation and teacher performance. The results of data analysis show that there is a significant relationship between motivation and teacher performance. Intrinsic motivation, such as a sense of responsibility and job satisfaction, has a greater influence than extrinsic motivation such as salary and incentives. High teacher performance is reflected in better lesson planning, use of innovative teaching methods and improved student learning outcomes. This study concludes that improving motivation, especially the intrinsic aspect, can be an effective strategy to improve the quality of education at Mts Al-Anwar Oku Timur.